Criminal Responsibility in the Corruption Case of Bumdes Lentong Village, Baharu District, Aceh Singkil Regency: (Analysis of Decision Number 5662 K/Pid.Sus/2022) - Eunike Enintha Pandia; Tata Reiforman Waruwu; Agus Armaini; Rodiatun Adawiyah (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
Every act must have the courage to carry out responsibility, the defendant who commits a criminal act of corruption must be given a prison sentence based on Article 2 of Law Number 20 of 2001 concerning Corruption Crimes. Decision Number 5662 K/Pid.Sus/2022, concerning the Corruption case committed by 2 (two) village officials from Lentong Village, Baharu District, Aceh Singkil Regency who committed corruption against BUMDes amounting to IDR 332,400,000 (three hundred and thirtytwo million four hundred thousand rupiah). This thesis is entitled: Criminal Responsibility in the Bumdes Corruption Case in Lentong Village, Baharu District, Aceh Singkil Regency (Analysis of Decision Number 5662 K/Pid.Sus/2022). The formulation of the problem is how the law protects defendants of criminal acts of corruption and how the Supreme Court Judge considers it in the case of Decision Number 5662 K/Pid.Sus/2022.